Communication about weight‐related issues with adult patients with obesity in general practice: A scoping review - Cecilie Sonne Lindberg; Annelli Sandbaek; Sissel Due Jensen; Jens Meldgaard Bruun; Pernille Andreassen (Wiley, 2023)
Abstract Background Primary care providers see patients with obesity in general practice every day but may be challenged regarding communication about obesity. The research question of this study is: how do general practitioners and general practice staff and adult patients with obesity communicate about weight‐related issues? Methods A scoping review approach was used, searching PubMed, Scopus and CINAHL for peer‐reviewed studies - of both quantitative and/or qualitative study designs, and published between 2001 and 2021. Results Twenty articles were included. The weight‐related issues discussed were by far physical issues, and only one study mentioned psychosocial issues. Most of the included studies contained information on who initiates the communication, how the weight‐related issues are addressed and handled, and also obstacles and challenges in relation to the communication. The studies lacked information of when the weight‐related issues are addressed and differences in views and experiences when discussing weight‐related issues in general practice. Conclusion Studies with the main focus communication about obesity and overall health in general practice are needed. Findings also indicate, that non‐stigmatizing communication tools and guidelines are needed on this area to promote these types of conservations.